A Real-world Prospective Cohort Study to Examine the Relationship Between Simple Physical Functioning Tests and Complications Following Abdominal Surgery - Broderick, Julie (My University, 2020)
BACKGROUND:The relationship between physical function and the development of complications in people after abdominal surgery is not well known. The objective of this study was to prospectively examine the relationship between simple physical functioning tests and complications following abdominal surgery. METHODS:Participants were recruited from an elective surgery waiting list. The following variables were measured pre-surgery; functional capacity (Six Minute Walk Test, 30 Second Sit to Stand Test), grip strength (hand dynamometer), self-report physical activity [International Physical Activity Questionnaire, (IPAQ)]. At 30 and 60 days post-operatively IPAQ and self-reported recovery were collected by telephone. Data related to complications and length of stay was extracted from the medical chart. RESULTS:Forty-nine participants (25M/18F) were recruited with a mean (SD) age of 59.5 (14.7) years. The complication rate was 41.9% (n = 18). Factors which differed between the complications and no complications groups were; longer operating time (p = 0.05),>2 co-morbidities (p = 0.033), body mass index >30 (p = 0.005), lower activity levels (p = 0.02), VO2 Peak (p = 0.017) and 6-minute walk distance (p = 0.019). There was an increased length of stay (p < 0.001) and sedentary time (p = 0.007) in the complications group. Activity levels reduced in the whole group (p < 0.001) even though self-report physical activity and recovery were high. CONCLUSION:A number of potentially modifiable physical functioning factors differed in the complication versus no complication groups. Future studies should evaluate whether optimizing physical functioning pre-operatively could alter complication rates and recovery in patients undergoing abdominal surgery.
PUBLISHED
Keywords: Abdominal surgery; Complications; Physical function; Recovery; Surgery; Cancer; Mobility impairment; Physical disability